The impact of demographic dissimilarity on service performance: a social network perspectives on communication network - Kang, Juhyun (Kansas State University, 2020)
Employee diversity issues have received attention from both academics and practitioners in hospitality. However, inconsistent effects of diversity on team and organizational performances indicate that further research is needed to achieve a better understanding about diversity. In order to explain the consequences of demographic dissimilarity, this study focuses on employees’ centrality in the formal and informal communication networks based on Social Identity Theory (SIT) and Job Demand Resource (JD-R) theory. The network analysis is used to assess structural positions of employees in work groups. The purpose of the study is to investigate how demographically dissimilar employees are placed in de-center of the formal and informal communication network, and how these communication networks impact in-role and proactive customer service performances. The current study targets at a total 106 hotel employees in the Mid-Eastern hotels in the U.S. Using a paper-pencil survey, questionnaires were distributed to hotel employees. For the social network analysis, a roster format was used to understand the respondents’ communication among their team members. In order to calculate the in-degree centrality in the communication network, UCINET 6.658 was used. The current study examined the negative impact of individual dissimilarity with team members on service performances via communication networks. Specifically, age dissimilarity and racial dissimilarity were negatively related to both formal and informal communication networks, while gender dissimilarity did not influence both formal and informal communication networks. Formal communication network mediated the relationship between age dissimilarity and in-role service performance, and informal communication network mediated the relationships between age dissimilarity and both in-role service performance and proactive customer service performance. In addition, formal and informal communication networks mediated the relationships between racial dissimilarity and both service performances. However, this study did not find the significant mediating effects of formal and informal communication networks in the relationships between gender dissimilarity and service performances. The contributions of the study to theory and practice are included along with limitations and directions for future research.
Keywords: Communication network; Service performance; Hotel employees; diversity